Correlation Between the Results from Screw Driving Sounding and Mackintosh Probe Tests - mohd satar, muhammad hatta; Aminaton Marto; Faizah Che Ros; Go Sakai; Masashi Shirahase (Journal of Advanced Research in Applied Mechanics, 2021)
The screw driving sounding (SDS) test is a new approach for shallow foundation sites such as road, school, mosque and housing projects. SDS test not just quick, but low cost and does not need experienced person to operate. By using the Industrial Revolution 4.0 (IR 4.0) innovation through automation during testing and using the cloud technology computing to process the information collected at the site, quality data are ensured. In this study, 33 sites were tested but results from Presint 9, Putrajaya site are presented in this paper. The correlation between SDS with Mackintosh Probe Test (MPT) value was made based on the correlation between energy obtained at 250 mm penetration (E0.25) and M value for soils at the sites. Results from Presint 9 site are compared with the MPT acquired from the previous soil investigation. The coefficient of determination, R2 = 0.4851 for Presint 9 site from the SDS test results are highly correlated with MPT test results. This discovery shows that the SDS test has great potential in soil investigation work in Malaysia with the advantage of IR 4.0 technology.